The Use of Ibrutinib in Extranodal Marginal Zone Lymphoma of the Ocular Adnexa with Multifocal Disease that is Refractory to Rituximab (Translation: The University of Toledo Journal of Medical Sciences, 2024)
Tumors of the ocular adnexa been well documented. The most common ocular adnexal lymphoma is extranodalmarginal zone B-cell lymphoma (EMZL), with about a quarter of those occurring in the conjunctiva. We present acase with a patient suspected ocular EMZL, confirmed with biopsy. Positron emission tomography (PET) scan wasperformed to evaluate for distal lesions and the patient was found to have multiple hypermetabolic lesionsthroughout the body. Treatment with rituximab was initiated, and after four weekly treatments, subsequent PETscan showed that the original hypermetabolic lesions remained and new lesions appeared. Rituximab was stoppedand ibrutinib started. After eight months of ibrutinib treatment, PET scan showed that the original hypermetaboliclesions had disappeared. 19 months from initiation of treatment, a new hilar lesion was found. This progressedinto bilateral hilar and mediastinal lymphadenopathy, which was seen on PET scan performed 29 months intotreatment. These findings remained stable 35 months post-initiation of treatment. The use of ibrutinib in thispatient that initially presented with a lesion in the conjunctiva resulted in an initial resolution of the originalsystemic hypermetabolic regions on PET scan. While more studies are needed on ibrutinib in the treatment ofocular EMZL, physicians should be aware of the presentation of this disease and the range of treatment modalities.
Keywords: Extranodal Marginal Zone Lymphoma; EMZL; Conjunctival Lymphoma; Rituximab; Ibrutinib